Transmembrane semaphorins, forward and reverse signaling: have a look both ways. - Battistini, C.; Tamagnone, L. (Cellular and molecular life sciences. CMLS, 2016)
Semaphorins are signaling molecules playing pivotal roles not only as axon guidance cues, but are also involved in the regulation of a range of biological processes, such as immune response, angiogenesis and invasive tumor growth. The main functional receptors for semaphorins are plexins, which are large single-pass transmembrane molecules. Semaphorin signaling through plexins-the "classical" forward signaling-affects cytoskeletal remodeling and integrin-dependent adhesion, consequently influencing cell migration. Intriguingly, semaphorins and plexins can interact not only in trans, but also in cis, leading to differentiated and highly regulated signaling outputs. Moreover, transmembrane semaphorins can also mediate a so-called "reverse" signaling, by acting not as ligands but rather as receptors, and initiate a signaling cascade through their own cytoplasmic domains. Semaphorin reverse signaling has been clearly demonstrated in fruit fly Sema1a, which is required to control motor axon defasciculation and target recognition during neuromuscular development. Sema1a invertebrate semaphorin is most similar to vertebrate class-6 semaphorins, and examples of semaphorin reverse signaling in mammalians have been described for these family members. Reverse signaling is also reported for other vertebrate semaphorin subsets, e.g. class-4 semaphorins, which bear potential PDZ-domain interaction motifs in their cytoplasmic regions. Therefore, thanks to their various signaling abilities, transmembrane semaphorins can play multifaceted roles both in developmental processes and in physiological as well as pathological conditions in the adult.